Rotigotine transdermal system as add-on to oral dopamine agonist in advanced Parkinson’s disease: an open-label study - Kim, Jong-Min (BMC Neurol, 2015)
BACKGROUND: Achieving optimal symptom control with minimal side effects is a major goal in clinical practice. Dual-agent dopamine receptor agonist (DA) therapy in Parkinson’s disease (PD) may represent a promising approach to treatment, as the combination of different pharmacokinetic/pharmacological profiles may result in a lesser need for high dosages and, accordingly, may be well tolerated. The objective of the current study was to investigate safety and efficacy of rotigotine transdermal system as add-on to oral DA in patients with advanced PD inadequately controlled with levodopa and low-dose oral DA. METHODS: PD0015 was an open-label, multinational study in patients with advanced-PD and sleep disturbance or early-morning motor impairment. Patients were titrated to optimal dose rotigotine (≤8 mg/24 h) over 1–4 weeks and maintained for 4–7 weeks (8-week treatment). Dosage of levodopa and oral DA (pramipexole ≤1.5 mg/day, ropinirole ≤6.0 mg/day) was stable. Primary variable was Clinical Global Impressions (CGI) item 4: side effects, assessing safety. Other variables included adverse events (AEs), Patient Global Impressions of Change (PGIC), Unified Parkinson’s Disease Rating Scale (UPDRS) II and III, Parkinson’s Disease Sleep Scale (PDSS-2), Pittsburgh Sleep Quality Index (PSQI), and “off” time. RESULTS: Of 90 patients who received rotigotine, 79 (88%) completed the study; 5 (6%) withdrew due to AEs. Most (83/89; 93%) had a CGI-4 score <3 indicating that rotigotine add-on therapy did not interfere with functioning; 6 (7%) experienced drug-related AEs that interfered with functioning (score ≥3). AEs occurring in ≥5% were application site pruritus (13%), dizziness (10%), orthostatic hypotension (10%), nausea (8%), dyskinesia (8%), and nasopharyngitis (6%). Numerical improvements in motor function (UPDRS III), activities of daily living (UPDRS II), sleep disturbances (PDSS-2, PSQI), and reduction in “off” time were observed. The majority (71/88; 81%) improved on PGIC. CONCLUSIONS: Addition of rotigotine transdermal system to low-dose oral DA in patients with advanced-PD was feasible and may be associated with clinical benefit. TRIAL REGISTRATION: ClinicalTrials.gov identifier NCT01723904. Trial registration date: November 6, 2012. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12883-015-0267-7) contains supplementary material, which is available to authorized users.